La proyección del Reglamento de IA sobre la Administración Pública: el Principio de explicabilidad aplicado al procedimiento administrativo - Mendilibar Navarro, Patricia (2025)
The AI Regulation has been a step forward in the regulation of artificial intelligence in the European Union. This paper analyzes the impact of this regulation on the use of AI by the public administration, particularly with regard to the explainability and motivation of decisions made with AI systems. The paper addresses the Regulation’s failure to address the risks of using AI in administrative procedures and identifies the shortcomings of Article 86 of the Regulation in relation to the need to justify and explain certain elements of the algorithmic administrative procedure so that it is understandable to citizens.